2010
DOI: 10.1093/humrep/deq310
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and metabolic profile of South Asian women with polycystic ovary syndrome (PCOS): results of a large database from a specialist Endocrine Clinic

Abstract: Young indigenous South Asians with PCOS have greater odds of being centrally obese, with a third having the MetS that bears no relationship to the androgenic phenotype. Significant predictors for MetS within the PCOS cohort are advancing age, obesity determined by the Asian cut off (BMI >25 kg/m(2)) and AN, while family history of diabetes, hyperandrogenism and elevated SHBG have no predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
114
5
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 37 publications
10
114
5
3
Order By: Relevance
“…Although normal cycling hyperandrogenic women (Hyperandrogenism and PCO morphology) had a significantly lower incidence of obesity than the other phenotypes, the prevalence of metabolic syndrome was similar in all phenotypes. In contrast to a large USA study, the data of which reported a two-fold increased risk of metabolic syndrome in hyperandrogenic women, this study did not reveal any link between plasma testosterone and the occurrence of metabolic syndrome (44).…”
Section: Pathogenesis Of Metabolic Syndrome In Adolescent Pcos Womencontrasting
confidence: 99%
“…Although normal cycling hyperandrogenic women (Hyperandrogenism and PCO morphology) had a significantly lower incidence of obesity than the other phenotypes, the prevalence of metabolic syndrome was similar in all phenotypes. In contrast to a large USA study, the data of which reported a two-fold increased risk of metabolic syndrome in hyperandrogenic women, this study did not reveal any link between plasma testosterone and the occurrence of metabolic syndrome (44).…”
Section: Pathogenesis Of Metabolic Syndrome In Adolescent Pcos Womencontrasting
confidence: 99%
“…In a recent study looking into phenotype and metabolic profile of South Asian women with PCOS, young indigenous South Asians with PCOS have greater odds of being centrally obese compared with BMImatched controls, with a third having metabolic syndrome that bears no relationship with the androgenic phenotype. The significant predictors for metabolic syndrome within the PCOS cohort were advancing age, obesity determined by the Asian cut off (BMI O25 kg/m 2 ), and acanthosis nigricans, while family history of diabetes, hyperandrogenism, and elevated SHBG did not have any predictive value (43), suggesting that we also have to factor ethnicity into equation. However, whether metabolic syndrome confers a CVR over and above the sum of its parts is still unclear.…”
Section: Metabolic Syndrome and Pcosmentioning
confidence: 95%
“…Multiple studies throughout the world indicated that several factors including ethnicity might contribute to these different inferences due to genetic polymorphisms [22][23][24] stressing on the fact that the association between metabolic and neuroendocrinological abnormalities with PCOS may vary between different population groups in different areas. However, only a few studies are available from the South Asian countries and the Indian subcontinent that provided information regarding the differential relationship between the neuroendocrinological and metabolic profile among PCOS patients in these regions [25,26]. Keeping these factors in mind, we aimed to analyze the neuroendocrinological abnormalities in the PCOS patients in our population group in eastern part of the country and find out their links with metabolic parameters like insulin resistance and lipid profile, and markers for body fat distribution like BMI and WHR.…”
mentioning
confidence: 99%